2022
DOI: 10.1103/physreva.105.023111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic-algorithm retrieval of the molecular alignment distribution with high-order harmonics generated from transiently aligned CO2 molecules

Abstract: Using genetic algorithm, we propose a method to retrieve the alignment distribution of transiently aligned CO2 molecules from the high-order harmonic generation (HHG) spectra. The retrieval method is based on the quantitative rescattering (QRS) model where averaged photorecombination transition dipole can be factored out from the parallel (or perpendicular) harmonic spectra after the propagation of the harmonic fields in the gas medium. We examine how the retrieved alignment distributions are affected by uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The high-order harmonic signal measured in the macroscopic molecular ensemble in the laboratory frame is a convolution of the single molecular signal with the alignment distribution. [43,44] To more precisely study the influence of the alignment effect on harmonic ellipticity, we calculate the molecular alignment distribution to exclude ambiguity due to imperfect alignment. In our calculation, we set the alignment degree cos 2 θ = 0.65, which can be easily achieved in the experiment.…”
Section: -3mentioning
confidence: 99%
“…The high-order harmonic signal measured in the macroscopic molecular ensemble in the laboratory frame is a convolution of the single molecular signal with the alignment distribution. [43,44] To more precisely study the influence of the alignment effect on harmonic ellipticity, we calculate the molecular alignment distribution to exclude ambiguity due to imperfect alignment. In our calculation, we set the alignment degree cos 2 θ = 0.65, which can be easily achieved in the experiment.…”
Section: -3mentioning
confidence: 99%
“…To date, several methods have been reported to measure molecular rotational temperature in experiment, for instance, using the coherent anti-Stokes Raman scattering (CARS) [28][29][30] and degenerate four-wave mixing (DFWM) [31] processes and also using the Fourier spectrum of time-dependent HHG signals [32] . A simultaneous measurement of molecular rotational temperature and pump laser intensity is also demonstrated from the HHG signals [33][34][35] and the molecular alignment echo measurement [36] . However, these methods are still limited by their inherent restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…[52] Jiang et al investigated the HHG from the aligned CO 2 molecule driven by a linearly polarized laser and found that the molecular polarization can be determined by the harmonic polarization state. [53] Son et al studied elliptically polarized high-order harmonics from aligned molecules irradiated by a linearly polarized driving field, and the physical mechanism of elliptically polarized harmonics is the amplitude and phase of harmonics. [54] However, the generation of elliptically polarized high-order harmonics, modulation of polarization characteristics, and basic principles of molecules driven by linearly polarized lasers must be studied.…”
Section: Introductionmentioning
confidence: 99%